Aplikasi Teknik zikir dalam Konseling Terhadap Kesehatan Mental - Wenda Asmita; Irman Irman (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
Human life is filled with various problems, sometimes there are humans who deal with it mediocrely and sometimes there are those that even lead to mental health disorders. The purpose of this research is to look at the use of the Recitation Technique for Mental Health. This can happen to anyone, anytime and anywhere. So of course an individual needs to have an alternative that will help him overcome this. Islamic counseling has an answer to the problem of mental health disorders, one of which is counseling with remembrance. This study uses the literature study method which helps in making it easier for the reader to know what aspects of the application of counseling techniques of remembrance to improve mental health. So that individuals or counselors can minimize mental health disorders by implementing counseling with this remembrance.